Glue-free glued fiberboard based on fiber pretreatment and preparation method of glue-free glued fiberboard
Through the dispersion, dissolution, and ciliary regeneration treatment of wood fibers, combined with suitable drying and hot pressing conditions, the problem of poor performance of the deadly-free fiberboard is solved, and the preparation of the glue-free fiberboard with excellent mechanical properties and water resistance is achieved.
Patent Information
- Application Number
- CN202411522536.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Existing legacy-free fiberboards have problems such as high hygroscopicity, poor dimensional stability, high cost and prone to mold, and cellulose fails to participate in the self-gluing process, affecting the performance of the board.
Lignocellulose fibers are dissolved in NaOH aqueous solution, followed by fibrillary dissolving treatment in NaOH/urea aqueous solution, and ciliary regeneration under the action of low concentration of acid, followed by drying to an appropriate moisture content, and then hot pressure is carried out Forming, forming rubber-free fiberboard with excellent mechanical properties and water resistance.
It significantly improves the self-gluing performance of glueless plywood fiberboard, improves the static curve strength, elastic modulus and water absorption and expansion rate of the board, and improves the mechanical properties and moisture stability of the board.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of artificial boards, and specifically relates to a glue-free plywood and a preparation method thereof, and in particular to a glue-free plywood based on fiber pretreatment and a preparation method thereof. Background Art
[0002] my country is a producer and consumer of wood-based panels, among which plywood is the largest wood-based panel and fiberboard is the second largest wood-based panel. Urea-formaldehyde resin, phenol-formaldehyde resin and melamine resin are mostly used as adhesives in the production of wood-based panels, all of which are adhesives containing formaldehyde. Especially for fiberboard, 90% of its production uses urea-formaldehyde resin adhesives, and formaldehyde pollution has become the most concerned issue for consumers. In recent years, formaldehyde-free wood-based panels have become an important development direction, including biomass adhesives, polyisocyanate resin (MDI) adhesives and other alternatives to formaldehyde adhesives. However, there are generally problems such as high hygroscopicity, poor dimensional stability, and high cost. Moreover, biomass adhesives based on soybean meal adhesives are prone to mold, and MDI adhesives are brittle, so the market share of formaldehyde-free fiberboards is very low. Therefore, the development of new formaldehyde-free or even glue-free fiberboards has become an urgent need for green production and quality and efficiency improvement in the fiberboard industry.
[0003] The main raw material of fiberboard is wood and bamboo fiber, which contains cellulose, lignin and hemicellulose. During the hot pressing process, lignin and hemicellulose are degraded under the action of moisture and heat, and the degradation products are self-bonded to form glue-free plywood. However, since the surface of cellulose contains a large number of hydroxyl groups, these hydroxyl groups do not play a role in improving performance during bonding, and due to the hygroscopicity of hydroxyl groups, after the board is formed, it is easy to absorb water and swell, resulting in poor performance of the board. Therefore, the development of the glue-free plywood industry needs to improve the stability of its performance.
[0004] Fiber pretreatment can significantly improve the self-bonding efficiency. However, general pretreatment methods are aimed at improving the degradation efficiency of lignin and hemicellulose so that the degradation products can act as adhesives. However, the failure of cellulose to participate in the self-bonding process is an important reason affecting the self-bonding performance. Therefore, effective fiber pretreatment technology and the preparation method of high-performance glue-free bonded fiberboard still need to be developed. Summary of the invention
[0005] The present invention has been developed in view of the above problems, and its purpose is to provide a preparation method based on fiber pretreatment and a glue-free plywood with excellent mechanical properties and water resistance prepared thereby.
[0006] In order to achieve the above-mentioned invention object, the present invention provides a method for preparing a non-glue fiberboard, which comprises: immersing wood fiber in a NaOH aqueous solution with a mass concentration of 0.8% to 1.5%, performing a decomposition treatment at a temperature of 85°C to 95°C for 2h to 4h, and filtering to obtain decomposition fibers; immersing the decomposition fibers in a NaOH / urea / water solution with a mass ratio of (5 to 9):12:(79 to 83), performing a fiber dissolution treatment at a temperature of -18°C to -5°C for 4h to 8h, adding a certain amount of low-concentration acid at room temperature for cilia regeneration treatment, and filtering to obtain cilia regenerated fibers; rinsing the cilia regenerated fibers with water until the pH is neutral, filtering, and drying at a temperature of 50°C to 70°C until the fiber moisture content is 8% to 15%, thereby obtaining pretreated fibers; and breaking up and paving the pretreated fibers and hot pressing them to obtain the non-glue fiberboard, wherein the hot pressing temperature is 180°C to 200°C, and the hot pressing pressure is 5MPa to 9MPa.
[0007] Furthermore, the solid-liquid ratio of wood fiber to NaOH aqueous solution is 1g:(50-100)mL. In addition, the solid-liquid ratio of debonded fiber to NaOH / urea / water solution is 1g:(50-100)mL. Since the mass change of wood fiber during debonding can be ignored, as an alternative, the solid-liquid ratio of wood fiber to NaOH / urea / water solution is (50-100)mL. Furthermore, the solid-liquid ratio of wood fiber to NaOH aqueous solution is 1g:70mL. The solid-liquid ratio of debonded fiber to NaOH / urea / water solution is 1g:70mL.
[0008] Furthermore, the mass concentration of the NaOH aqueous solution is 1%, the decomposition treatment temperature is 90°C, and the treatment time is 3 hours; the mass ratio of NaOH / urea / water solution is 7:12:81, the fiber dissolution treatment temperature is -12°C, and the treatment time is 6 hours.
[0009] Furthermore, the drying treatment temperature is 55°C to 65°C, and furthermore, the drying treatment temperature is 60°C.
[0010] If the solid-liquid ratio of wood fiber to NaOH aqueous solution is too low, it is difficult to completely wet the fiber, resulting in poor decomposition effect; if it is too high, it will cause waste of alkaline solution; if the decomposition time is too short, lignin and hemicellulose will not be depolymerized enough, affecting the dissolution and regeneration of cellulose at low temperature; if the temperature is too high and the time is too long, it will lead to excessive degradation of lignin and hemicellulose, and the loss of lignin into small molecules, affecting the bonding performance.
[0011] If the material-liquid ratio of the fiber to the NaOH aqueous solution is too low, it will be difficult to completely wet the fiber during the treatment process. If it is too high, the permeability of the solution on the fiber surface will be too high, which will seriously damage the crystallinity of the surface cellulose and reduce the self-bonding performance. If the dissolution treatment time is too short, the cellulose on the fiber surface will be dissolved and regenerated into fewer fibrils, making it difficult to form strong hydrogen bonds. If the time is too long, more surface cellulose will be dissolved, the overall crystallinity of the fiber will be affected, and the self-bonding performance will be reduced. Therefore, a reasonable material-liquid ratio and treatment time should be matched to ensure the optimal debonding effect.
[0012] The processed fibers are used to make glue-free plywood. Therefore, too high a drying temperature will cause serious fiber clumping, which is not conducive to fiber laying and will lead to uneven density of self-plywood. Too low a drying temperature will take too long to dry the fibers, thereby increasing manufacturing energy consumption.
[0013] By ensuring that the fiber has a moisture content of 8% to 15%, water molecules play a plasticizing role in the hot pressing process of preparing glue-free fiberboard, which can reduce the glass transition temperature of lignin degradation products, promote lignin flow, and improve the self-bonding efficiency of hemicellulose and lignin degradation products; in addition, water molecules play an interfacial transition role during the hot pressing volatilization process, promoting the formation of a solid-liquid stable interface to a solid-solid interface. However, if the moisture content is too high, it is difficult to remove the water in a short hot pressing time, resulting in bubbling of the self-bonding fiberboard.
[0014] It is preferred to ensure that the fiber moisture content is 12% to 15% during the drying process, which can better ensure that water acts as a medium to achieve solid-liquid exchange between the solid regenerated cilia during the hot pressing process. During the exchange process, water molecules introduce a hydroxyl group and form a hydrogen bond with another hydroxyl group during the departure process, thereby achieving fiber self-bonding.
[0015] If the hot pressing temperature is too low, lignin and hemicellulose are difficult to degrade, and the self-adhesive properties of the degradation products decrease. If the hot pressing temperature is too high, it is easy to cause carbonization of the fiber surface and blackening of the self-adhesive fiberboard.
[0016] Similarly, hot pressing pressure is also a very important factor. If the hot pressing pressure is too low, it will be difficult for the hydroxyl groups on the fibrillated surface to form strong hydrogen bonds. The boards formed with weak hydrogen bonds will easily absorb water and expand under high humidity conditions, affecting the performance of the self-adhesive boards.
[0017] Furthermore, the hot pressing temperature is 185° C. to 195° C., and the hot pressing pressure is 6 MPa to 8 MPa. Furthermore, the hot pressing temperature of hot pressing molding is 190° C., and the hot pressing pressure is 7 MPa.
[0018] Among them, H + Content and OH content of NaOH in NaOH / urea / water solution - The molar ratio of the content is (0.5-1):1, and the H+ The ion concentration is 0.8mol / L~1.3mol / L.
[0019] The low concentration acid may be a hydrochloric acid solution or a sulfuric acid solution.
[0020] As a specific example, the low-concentration acid is a sulfuric acid solution with a mass concentration of 4% to 6%, and further, the mass concentration of the sulfuric acid solution is 5%.
[0021] As another specific example, the low-concentration acid is a sulfuric acid solution having a molar concentration of 0.43 mol / L to 0.64 mol / L, and further, the molar concentration of the sulfuric acid solution is 0.54 mol / L.
[0022] Furthermore, the low concentration acid can be added and the treatment time can be maintained for 0.1 h to 1 h.
[0023] The low-concentration acid can be set to correspond to the specific amount of NaOH / urea / water solution added. Once the low-concentration acid is added, it will neutralize the NaOH and quickly regenerate the fiber. Therefore, the treatment time is not limited here.
[0024] Specifically, the wood fiber may be one or more of eucalyptus fiber, poplar fiber, fir fiber, masson pine fiber, miscellaneous wood fiber, and bamboo fiber.
[0025] Specifically, the drying process is performed in a constant temperature and humidity environment with a relative humidity of 60% to 80%.
[0026] As a further specific example, the constant temperature and humidity environment uses a constant temperature and humidity oven with a drying temperature of 60° C. and a relative humidity of 70%.
[0027] Specifically, the pretreated fiber has a laying thickness of 2 mm to 12 mm and a density of 0.8 to 1.2 g / cm 3 , the hot pressing time is 2-4 mm / min. More specifically, the paving thickness is 8-10 mm, and the density is 0.8-1.0 g / cm 3 .
[0028] The present invention also provides a glue-free fiberboard prepared by any of the above preparation schemes.
[0029] According to the research of the inventors, the improvement of fiber self-bonding performance depends on two factors. First, lignin and hemicellulose in the fiber are degraded at a certain temperature and humidity to form small molecules, and the degradation products are self-bonded. Second, cellulose is melted and regenerated to form fibrils on the fiber surface. The surface fibrillation greatly increases the hydroxyl group and activity of the fiber surface. The hydroxyl group forms hydrogen bonds, which improves the self-bonding performance.
[0030] After high temperature treatment with alkaline solution, hemicellulose and lignin on the fiber surface are partially degraded, exposing more cellulose on the fiber surface, while alkali / urea low temperature treatment can promote cellulose dissolution and regeneration under the action of acid, forming cellulose fibrils on the fiber surface, increasing the surface hydroxyl activity and greatly increasing the area of the self-bonding interface. After high and low temperature pretreatment, in the process of glue-free bonding, not only the degradation products of hemicellulose and lignin are self-bonded, but also the cellulose fibrils are self-bonded under the action of hydrogen bonds. The three major components in the fiber play a self-bonding role, which significantly improves the performance of glue-free plywood. Among them, the high temperature treatment time, temperature and concentration of alkaline solution are important influencing factors, and the concentration, temperature and time of alkali / urea low temperature treatment are the most important influencing factors for cellulose dissolution and regeneration. Insufficient high temperature treatment causes cellulose to be wrapped, making it difficult to dissolve and regenerate in the subsequent high temperature process. Excessive high temperature treatment will cause lignin degradation loss and affect the self-bonding of lignin degradation products. Insufficient low temperature treatment process makes cellulose difficult to dissolve, and too long low temperature treatment time will cause too much cellulose dissolution, which will destroy the crystallization of cellulose and reduce the mechanical strength of the fiber. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the following examples and comparative examples, the static bending strength test process of the prepared plate is as follows:
[0033] Cut the plate into a size of 5mm×60mm×t (t is thickness), adjust the support span of the mechanical testing machine to at least 20 times the thickness of the specimen, place the specimen on the support, with the long axis of the specimen perpendicular to the supporting roller and the center point of the specimen under the loading roller, load the entire specimen at a constant speed, adjust the loading speed, reach the maximum load within 1 minute, record the maximum load, and take the average value of 5 parallel tests.
[0034] Static bending strength formula:
[0035] σ: static bending strength of specimen, MPa;
[0036] F max : Maximum load when the specimen is destroyed, N;
[0037] l: distance between two supports, mm;
[0038] b: specimen width, mm;
[0039] t: specimen thickness, mm.
[0040] The elastic modulus test method of the prepared plate is the same as that of the static bending strength.
[0041] Elastic modulus formula:
[0042] E b : elastic modulus of the specimen, MPa;
[0043] l: distance between two supports, mm;
[0044] b: specimen width, mm;
[0045] t: specimen thickness, mm;
[0046] F 2 -F 1 : The increase in load in the straight line segment of the load-deflection curve, N;
[0047] a 2 -a 1 : The increase in deformation in the middle of the specimen, that is, the force F 2 ~F 1 Deformation of the interval specimen, mm.
[0048] The test method for the water absorption expansion rate of the prepared board is:
[0049] Cut the board into 20mm×20mm size, immerse it in a water tank with a pH value of 7±1 and a temperature of (20±1)℃, with the upper part of the specimen below the water surface by (25±5)mm. Soak for 24h. After immersion, take out the specimen, wipe off the water attached to the surface, and measure its thickness at the original measuring point. The water absorption expansion rate is the ratio of the increase in thickness after water absorption to the thickness before water absorption.
[0050] Water absorption expansion formula:
[0051] T: water absorption thickness expansion rate, %;
[0052] t 1 : Thickness of the specimen before immersion, mm;
[0053] t 2 : Thickness of the specimen after immersion in water, mm.
[0054] Example 1
[0055] (1) 16 g of poplar fiber was immersed in 800 mL of a 0.8% NaOH aqueous solution, the temperature was raised to 85° C. and maintained for 2 h for decomposition treatment, and decomposition fibers were obtained by filtration.
[0056] (2) Prepare a NaOH / urea / water solution with a mass ratio of NaOH / urea / water of 5:12:79, immerse the poplar fibers disintegrated in step (1) in 800 mL of the NaOH / urea / water solution, cool to -5°C and keep for 4 h to dissolve the fibers, return to room temperature of 25°C, add 100 mL of a 4% sulfuric acid solution and keep for 10 min to regenerate the cilia, and filter to obtain the regenerated cilia fibers.
[0057] (3) The ciliary regenerated fiber is rinsed with water until the pH is neutral, filtered, placed in a constant temperature and humidity oven, and the drying temperature is set to 50°C and the relative humidity is set to 60% for drying. The moisture content of the fiber is monitored during the process. The drying is stopped when the moisture content reaches 8%, and the pretreated fiber is taken out.
[0058] (4) The pretreated fibers were scattered and laid in a hot pressing mold with a mold size of 100 mm × 100 mm × 2 mm and a density of 0.8 g / cm 3 The hot pressing temperature is 180°C, the hot pressing pressure is 5 MPa, and the hot pressing time is 2 mm / min. After the hot pressing temperature is allowed to stand at room temperature, a glue-free poplar fiberboard is obtained.
[0059] performance:
[0060] Static bending strength: 76MPa
[0061] Elastic modulus: 3.5GPa
[0062] 24h moisture expansion rate: 8.1%
[0063] Example 2
[0064] (1) 16 g of bamboo fiber was immersed in 1600 mL of a 1.5% NaOH aqueous solution, the temperature was raised to 95° C. and maintained for 4 h for decomposition treatment, and the decomposition fiber was obtained by filtration.
[0065] (2) Prepare a NaOH / urea / water solution with a mass ratio of NaOH / urea / water of 9:12:83, immerse the poplar fibers disintegrated in step (1) in 1600 mL of the NaOH / urea / water solution, cool to -18°C and keep for 8 h to dissolve the fibers, return to room temperature of 25°C, add 400 mL of a 6% sulfuric acid solution and keep for 60 min to regenerate the cilia, and filter to obtain the regenerated cilia fibers.
[0066] (3) The ciliary regenerated fiber is rinsed with water until the pH is neutral, filtered, placed in a constant temperature and humidity oven, and the drying temperature is set to 70°C and the relative humidity is set to 80% for drying. The moisture content of the fiber is monitored during the process. The drying is stopped when the moisture content reaches 12%, and the pretreated fiber is taken out.
[0067] (4) The pretreated fibers were scattered and laid in a hot pressing mold with a mold size of 100 mm × 100 mm × 12 mm and a density of 1.2 g / cm 3 The hot pressing temperature is 200°C, the hot pressing pressure is 9 MPa, and the hot pressing time is 4 mm / min. After it is allowed to stand at room temperature, the glue-free bonded bamboo fiberboard is obtained.
[0068] performance:
[0069] Static bending strength: 125MPa
[0070] Elastic modulus: 9.2GPa
[0071] 24h moisture expansion rate: 6.2%
[0072] Example 3
[0073] (1) 16 g of fir fiber was immersed in 800 mL of a 0.8% NaOH aqueous solution, the temperature was raised to 85° C. and maintained for 2 h for decomposition treatment, and decomposition fiber was obtained by filtration.
[0074] (2) Prepare a NaOH / urea / water solution with a mass ratio of NaOH / urea / water of 5:12:79, immerse the poplar fibers disintegrated in step (1) in 800 mL of the NaOH / urea / water solution, cool to -5°C and keep for 4 h to dissolve the fibers, return to room temperature of 25°C, add 100 mL of a 3% hydrochloric acid solution and keep for 30 min to regenerate the cilia, and filter to obtain the regenerated cilia fibers.
[0075] (3) The ciliary regenerated fiber is rinsed with water until the pH is neutral, filtered, placed in a constant temperature and humidity oven, and the drying temperature is set to 55°C and the relative humidity is set to 60% for drying. The moisture content of the fiber is monitored during the process. The drying is stopped when the moisture content reaches 12%, and the pretreated fiber is taken out.
[0076] (4) The pretreated fibers were scattered and laid in a hot pressing mold with a mold size of 100 mm × 100 mm × 8 mm and a density of 1.0 g / cm 3 The hot pressing temperature is 185°C, the hot pressing pressure is 6MPa, and the hot pressing time is 2mm / min. After it is allowed to stand at room temperature, the glue-free glued fir fiberboard is obtained.
[0077] performance:
[0078] Static bending strength: 109MPa
[0079] Elastic modulus: 6.5GPa
[0080] 24h moisture expansion rate: 7.6%
[0081] Example 4
[0082] (1) 16 g of fir fiber was immersed in 800 mL of a 1.2% NaOH aqueous solution, the temperature was raised to 95° C. and maintained for 4 h for decomposition treatment, and decomposition fiber was obtained by filtration.
[0083] (2) Prepare a NaOH / urea / water solution with a mass ratio of NaOH / urea / water of 5:12:79, immerse the poplar fibers disintegrated in step (1) in 800 mL of the NaOH / urea / water solution, cool to -18°C and keep for 6 h to dissolve the fibers, return to room temperature of 25°C, add 400 mL of a 4% sulfuric acid solution and keep for 30 min to regenerate the cilia, and filter to obtain the regenerated cilia fibers.
[0084] (3) The ciliary regenerated fiber is rinsed with water until the pH is neutral, filtered, placed in a constant temperature and humidity oven, and the drying temperature is set to 65°C and the relative humidity is set to 80% for drying. The moisture content of the fiber is monitored during the process. The drying is stopped when the moisture content reaches 15%, and the pretreated fiber is taken out.
[0085] (4) The pretreated fibers were scattered and laid in a hot pressing mold with a mold size of 100 mm × 100 mm × 10 mm and a density of 0.9 g / cm 3 The hot pressing temperature was 195°C, the hot pressing pressure was 8 MPa, and the hot pressing time was 4 mm / min. After the hot pressing temperature was allowed to stand at room temperature, the glue-free plywood fiberboard was obtained.
[0086] performance:
[0087] Static bending strength: 90MPa
[0088] Elastic modulus: 3.8GPa
[0089] 24h moisture expansion rate: 9.4%
[0090] Example 5
[0091] (1) 16 g of poplar fiber was immersed in 1000 mL of a 1% NaOH aqueous solution, the temperature was raised to 90° C. and maintained for 3 h for decomposition treatment, and the decomposition fiber was obtained by filtration.
[0092] (2) Prepare a NaOH / urea / water solution with a mass ratio of NaOH / urea / water of 7:12:81, immerse the poplar fibers disintegrated in step (1) in 1000 mL of the NaOH / urea / water solution, cool to -12°C and keep for 6 h to dissolve the fibers, return to room temperature of 25°C, add 200 mL of a 5% sulfuric acid solution and keep for 30 min to regenerate the cilia, and filter to obtain the regenerated cilia fibers.
[0093] (3) The ciliary regenerated fiber is rinsed with water until the pH is neutral, filtered, placed in a constant temperature and humidity oven, and the drying temperature is set to 60° C. and the relative humidity is set to 70% for drying. The moisture content of the fiber is monitored during the process. The drying is stopped when the moisture content reaches 12%, and the pretreated fiber is taken out.
[0094] (4) The pretreated fibers were scattered and laid in a hot pressing mold with a mold size of 100 mm × 100 mm × 8 mm and a density of 0.8 g / cm 3 The hot pressing temperature was 190°C, the hot pressing pressure was 7 MPa, and the hot pressing time was 3 mm / min. After the hot pressing temperature was allowed to stand at room temperature, a glue-free poplar fiberboard was obtained.
[0095] performance:
[0096] Static bending strength: 89MPa
[0097] Elastic modulus: 6.8GPa
[0098] 24h moisture expansion rate: 7.6%
[0099] Comparative Example 1
[0100] The fiberboard was prepared by using untreated poplar fiber in the same manner as in Example 5. The test results are as follows:
[0101] Static bending strength: 32MPa
[0102] Elastic modulus: 2.0GPa
[0103] 24h moisture expansion rate: 40.5%
[0104] Comparative Example 2
[0105] The difference from Example 5 is that the fiber is dried until the moisture content is 8%. The test results are as follows:
[0106] Static bending strength: 65MPa
[0107] Elastic modulus: 4.8GPa
[0108] 24h moisture expansion rate: 10.5%
[0109] Comparative Example 3
[0110] The difference from Example 5 is that the fiber is dried until its moisture content is 7%. The test results are as follows:
[0111] Static bending strength: 57MPa
[0112] Elastic modulus: 3.1GPa
[0113] 24h moisture expansion rate: 15.8%
[0114] Comparative Example 4
[0115] The difference from Example 1 is that the NaOH aqueous solution is 700 mL, and the test results are:
[0116] Static bending strength: 68MPa
[0117] Elastic modulus: 2.4GPa
[0118] 24h moisture expansion rate: 12.8%
[0119] Comparative Example 5
[0120] The difference from Example 1 is that the decontamination time is 1 hour, and the test results are:
[0121] Static bending strength: 70MPa
[0122] Elastic modulus: 3.4GPa;
[0123] 24h moisture expansion rate: 11.4%
[0124] Comparative Example 6
[0125] The difference from Example 4 is that the decomposition time is 5 hours, the decomposition temperature is 100°C, and the test results are:
[0126] Static bending strength: 82MPa
[0127] Elastic modulus: 3.7GPa
[0128] 24h moisture expansion rate: 15.1%
[0129] Comparative Example 7
[0130] The difference from Example 1 is that the NaOH / urea / water solution is 700 mL. The test results are:
[0131] Static bending strength: 70MPa
[0132] Elastic modulus: 2.8GPa
[0133] 24h moisture expansion rate: 17.2%
[0134] Comparative Example 8
[0135] The difference from Example 1 is that the dissolution time is 3h, and the test results are:
[0136] Static bending strength: 73MPa
[0137] Elastic modulus: 3.3GPa
[0138] 24h moisture expansion rate: 9.4%
[0139] Comparative Example 9
[0140] The difference from Example 2 is that the dissolution time is 9h, and the test results are:
[0141] Static bending strength: 94MPa
[0142] Elastic modulus: 6.5GPa
[0143] 24h moisture expansion rate: 7.5%
[0144] Comparative Example 10
[0145] The difference from Example 2 is that the drying temperature is 80°C. The test results are:
[0146] Static bending strength: 115MPa
[0147] Elastic modulus: 9.9GPa
[0148] 24h moisture expansion rate: 5.9%
[0149] Comparative Example 11
[0150] The difference from Example 1 is that the hot pressing temperature is 170°C. The test results are as follows:
[0151] Static bending strength: 64MPa
[0152] Elastic modulus: 2.5GPa
[0153] 24h moisture expansion rate: 35.2%
[0154] Comparative Example 12
[0155] The difference from Example 2 is that the hot pressing temperature is 210°C. The test results are:
[0156] Black
[0157] Static bending strength: 117MPa
[0158] Elastic modulus: 9.5GPa
[0159] 24h moisture expansion rate: 3.2%
[0160] Comparative Example 13
[0161] The difference from Example 1 is that the hot pressing pressure is 4 MPa. The test results are as follows:
[0162] Static bending strength: 72MPa
[0163] Elastic modulus: 5.1GPa
[0164] 24h moisture expansion rate: 12.5%
[0165] Comparative Example 14
[0166] The difference from Example 2 is that the hot pressing pressure is 10 MPa. The test results are:
[0167] Bubbling
[0168] Static bending strength: 120MPa
[0169] Elastic modulus: 10.5GPa
[0170] 24h moisture expansion rate: 8.5%.
Claims
1. A method for preparing glue-free plywood based on fiber pretreatment, It is characterized in that include: The wood fibers are immersed in a NaOH aqueous solution with a mass concentration of 0.8% to 1.5%, and after being subjected to a decomposition treatment at a temperature of 85° C. to 95° C. for 2 h to 4 h, the decomposition fibers are filtered to obtain decomposition fibers; The debonded fibers are immersed in a NaOH / urea / water solution with a mass ratio of (5-9):12:(79-83), and the fibers are dissolved at a temperature of -18°C to -5°C for 4h to 8h. A certain amount of low-concentration acid is added at room temperature to perform a cilia regeneration treatment, and the cilia regenerated fibers are obtained by filtration; The ciliary regenerated fiber is washed with water until the pH is neutral, filtered, and dried at 50°C to 70°C until the fiber moisture content is 8% to 15%, thereby obtaining pretreated fiber; The pretreated fibers are scattered and laid, and then hot-pressed to obtain the glue-free fiberboard, wherein the hot-pressing temperature is 180° C. to 200° C., and the hot-pressing pressure is 5 MPa to 9 MPa.
2. The preparation method according to claim 1, wherein The material-liquid ratio of wood fiber to NaOH aqueous solution is 1 g: (50-100) mL; The material-liquid ratio of the decomposed fiber to the NaOH / urea / water solution is 1 g: (50-100) mL.
3. The preparation method according to claim 1, wherein The fiber is dried until its moisture content is 12% to 15%.
4. The preparation method according to claim 1, wherein The hot pressing temperature is 185°C to 195°C, and the hot pressing pressure is 6MPa to 8MPa.
5. The preparation method according to claim 1, wherein The mass concentration of NaOH aqueous solution is 1%, the decomposition treatment temperature is 90°C, and the treatment time is 3h; the mass ratio of NaOH / urea / water solution is 7:12:81, the fiber dissolution treatment temperature is -12°C, and the treatment time is 6h; the solid-liquid ratio of wood fiber to NaOH aqueous solution is 1g:70mL; the solid-liquid ratio of decomposition fiber to NaOH / urea / water solution is 1g:70mL; the drying treatment temperature is 60°C; the hot pressing temperature is 190°C, and the hot pressing pressure is 7MPa.
6. The preparation method according to claim 1, wherein Low concentration of acid H + Content and OH content of NaOH in NaOH / urea / water solution - The molar ratio of the content is (0.5-1):1, and the H + The ion concentration is 0.8mol / L~1.3mol / L.
7. The preparation method according to claim 6, wherein The low concentration acid is a hydrochloric acid solution or a sulfuric acid solution.
8. The preparation method according to claim 1, wherein The wood fiber is one or more of eucalyptus fiber, poplar fiber, fir fiber, masson pine fiber, miscellaneous wood fiber and bamboo fiber.
9. The preparation method according to claim 1, wherein The drying process is carried out in a constant temperature and humidity environment with a relative humidity of 60% to 80%.
10. The glue-free fiberboard prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for manufacturing rubber-free high-density fiberboard
CN103029196A
Method for preparing regenerated cellulose composite membrane by crop straws
CN103319738A
Production method of lignin-containing nano-crystalline cellulose fibril
CN109868667A
Activated lignin modified phenolic resin wood adhesive and preparation method thereof
CN111285985A
Preparation method of reinforced and toughened bamboo-based automotive trim panel
CN118617838A
Cited By
Silicon resin modified super-hydrophobic impregnated paper laminated wood floor and production method thereof
CN121295892A
